In-vitro evaluation of the effect of okra (Abelmoschus esculentus L.) extract on periodontal cells: a comprehensive study of cellular and molecular impacts - Umut Ulaş Tosun; Sema Tuğçe Aydın; Ayşegül Tiryaki; Dilruba Baykara; Aleyna Yakut; Erkan Rayaman; Turgut Taşkın; Canan Ekinci Doğan; Oğuzhan Gündüz; Ömer Birkan Ağralı (BMC Complementary Medicine and Therapies)
Abstract Background This research assessed the potential role of okra (Abelmoschus esculentus L.) extract on periodontal tissue wound healing by evaluating its effects on human periodontal ligament fibroblast (hPDLF), human gingival fibroblast (hGF), and human osteoblast (hOB) cells in vitro. Methods The viability effect of okra extract on hPDLF, hGF, and hOB cells was determined using the MTT assay protocol. The highest viability concentrations were applied to hPDLF and hOB cells, and the expression levels of on type 1 collagen (COL1), bone morphogenetic protein 2 (BMP2), axis inhibition protein 2 (AXIN2), and fibroblast growth factor 2 (FGF2) proteins were determined through ELISA. The extract was also tested for antioxidant (CUPRAC, DPPH, FCR, and FRAP tests), acetylcholinesterase (AChE) inhibition, and antimicrobial properties, and its content was determined by HPLC-DAD. Results The viability results showed no significant difference between the okra extract-treated and control groups for all cell types. In hPDLF cells, higher expression levels of COL1 and AXIN2 in the okra extract-treated group compared to the control group, while BMP2 expression level was lower. In hOB cells, the extract-treated group had higher levels of COL1, BMP2, and AXIN2 expression than the control group. Conclusion It can be posited that okra extract may activate the Wnt/β-catenin signalling pathway and may have a beneficial impact on wound healing in periodontal tissues. However, extensive long-term in-vivo research on the activation of signalling pathways by okra extract in periodontal wound healing is required.